MOLECULAR PATHOGENESIS OF SECONDARY ACUTE PROMYELOCYTIC LEUKEMIA - Melanie Joannides; Ashley N Mays; Anita R Mistry; Syed Khizer Hasan; Andreas Reiter; Joseph L Wiemels; Carolyn A Felix; Francesco Lo-Coco; Neil Osheroff; Ellen Solomon; David Grimwade (Mediterranean Journal of Hematology and Infectious Diseases)
Balanced chromosomal translocations that generate chimeric oncoproteins are considered to be initiating lesions in the pathogenesis of acute myeloid leukemia. The most frequent is the t(15;17)(q22;q21), which fuses the PML and RARA genes, giving rise to acute promyelocytic leukemia (APL). An increasing proportion of APL cases are therapy-related (t-APL), which develop following exposure to radiotherapy and/or chemotherapeutic agents that target DNA topoisomerase II (topoII), particularly mitoxantrone and epirubicin. To gain insights into molecular mechanisms underlying the formation of the t(15;17) we mapped the translocation breakpoints in a series of t-APLs, which revealed significant clustering according the nature of the drug exposure. Remarkably, in approximately half of t-APL cases arising following mitoxantrone treatment for breast carcinoma or multiple sclerosis, the chromosome 15 breakpoint fell within an 8-bp “hotspot” region in PML intron 6, which was confirmed to be a preferential site of topoII-mediated DNA cleavage induced by mitoxantrone.  Chromosome 15 breakpoints falling outside the “hotspot”, and the corresponding RARA breakpoints were also shown to be functional topoII cleavage sites. The observation that particular regions of the PML and RARA loci are susceptible to topoII-mediated DNA damage induced by epirubicin and mitoxantrone may underlie the propensity of these agents to cause APL.